2017
DOI: 10.1210/jc.2017-01555
|View full text |Cite
|
Sign up to set email alerts
|

PTH(1–34) for Surgical Hypoparathyroidism: A 2-Year Prospective, Open-Label Investigation of Efficacy and Quality of Life

Abstract: This study demonstrates the efficacy and safety of PTH(1-34) to treat adult patients with postsurgical hypoparathyroidism. PTH(1-34) may improve their mental and physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 24 publications
3
53
1
6
Order By: Relevance
“…However, PTH interventions studies have shown conflicting results. An improved QoL following PTH therapy has been reported in open‐label cohort studies, but a causal relationship has so far not been proven in double‐blind, placebo‐controlled trials …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PTH interventions studies have shown conflicting results. An improved QoL following PTH therapy has been reported in open‐label cohort studies, but a causal relationship has so far not been proven in double‐blind, placebo‐controlled trials …”
Section: Discussionmentioning
confidence: 99%
“…interventions studies have shown conflicting results. An improved QoL following PTH therapy has been reported in open-label cohort studies,15,[30][31][32] but a causal relationship has so far not been proven in double-blind, placebo-controlled trials 13,33. We found a similar proportion of patients with Ns-HypoPT to be on permanent social security benefits as in the Norwegian study by Astor et al,5 although a higher proportion of our patients with PHP were on permanent security benefits compared with the Norwegian data (37% vs 25%, respectively).…”
mentioning
confidence: 82%
“…The risk of overtreatment are hypercalciuria, hyper-calcemia, kidney stones, and cardiac risk in patients at risk (38). The review published in 2019 using a Cochrane risk of bias showed that routine calcium and vitamin D supplementation statistically significant decreases the risk of developing transitory hypocalcemia and acute complications compare to calcium alone supplements or no supplements but it has a minor role in permanent severe forms (39). Others authors consider that actually the prevention of hypocalcemia starts intraoperatory with meticulous manipulation of parathyroid glands and their vessels (40)(41)(42).…”
Section: General Datamentioning
confidence: 99%
“…In fact, there have been many reports that used 1-34 PTH as intact PTH in vitro and in vivo experiments. [42][43][44] As shown in Fig. 5, a 40 ng/mL solution of PTH significantly induced the production of intracellular ROS in HUVEC.…”
Section: Cinacalcet and The Oxidized Albumin Ratio In Shpt Patientsmentioning
confidence: 77%